2016
DOI: 10.12659/ajcr.898864
|View full text |Cite
|
Sign up to set email alerts
|

Parent Misidentification Leading to the Breastfeeding of the Wrong Baby in a Neonatal Intensive Care Unit

Abstract: Patient: Male, 2 monthFinal Diagnosis: 2 month old 32 weeks’ gestational age preterm infantSymptoms: PrematurityMedication: —Clinical Procedure: Accidental breastfeeding of the wrong babySpecialty: Pediatrics and NeonatologyObjective:Diagnostic/therapeutic accidentsBackground:Because there are clear benefits to breast milk over formula for infants, the goal of the World Health Organization is to increase breastfeeding rates. As more women are breastfeeding and providing breast milk to newborns in hospitals, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
4
0
2
Order By: Relevance
“…O leite materno pode transmitir doenças conhecidas e desconhecidas e por isso, quando se é doado ou compartilhado, ele deve ser pasteurizado antes de ser dado à criança. O número de UTINS que utilizam o leite materno pasteurizado das doadoras dos bancos de leites aumentou nos últimos anos, porém muitas instituições ainda não adotaram essa medida seja por questões de custo, falta de disponibilidade, resistência dos pais em aceitar o leite doado, questões culturais, religiosas ou legais (Sauer et al, 2016).…”
Section: Introductionunclassified
“…O leite materno pode transmitir doenças conhecidas e desconhecidas e por isso, quando se é doado ou compartilhado, ele deve ser pasteurizado antes de ser dado à criança. O número de UTINS que utilizam o leite materno pasteurizado das doadoras dos bancos de leites aumentou nos últimos anos, porém muitas instituições ainda não adotaram essa medida seja por questões de custo, falta de disponibilidade, resistência dos pais em aceitar o leite doado, questões culturais, religiosas ou legais (Sauer et al, 2016).…”
Section: Introductionunclassified
“…5 Although the risk of infant misidentification ranges from 20.6% to 72.9% for average daily census, 6 the risk for misidentification is not just limited to being sent home with the incorrect mother/parents but also to being provided incorrect medications/breast milk or being given the wrong infant to breastfeed. [6][7][8][9] When analyzing infant security systems, teams must also consider the potential that security measures may induce unnecessary fear or anxiety in new mothers and family members. Analyzing the security processes surrounding infant identification and abduction prevention can provide valuable insight into the potentials for failure as well as the areas where patient perception is different from the presented realities.…”
mentioning
confidence: 99%
“…In 1953, Byrne reported that 12% of medication administration errors were “medication given to the wrong patient.” Our willingness to publish wrong patient errors suggests a readiness to learn from our mistakes and change the system within which we work. Previous articles have reported the wrong patient undergoing an invasive cardiac electrophysiologic study despite her attempts at refusal, an inadvertent HLA‐incompatible allogeneic bone marrow transplant from the incorrect donor, the wrong infant breastfed in the neonatal intensive care unit after a bed move, and using the wrong ABO group red blood cells (RBCs) to prime the bypass circuit for an infant undergoing congenital heart surgery …”
mentioning
confidence: 99%
“…Our willingness to publish wrong patient errors suggests a readiness to learn from our mistakes and change the system within which we work. Previous articles have reported the wrong patient undergoing an invasive cardiac electrophysiologic study despite her attempts at refusal, 4 an inadvertent HLAincompatible allogeneic bone marrow transplant from the incorrect donor, 5 the wrong infant breastfed in the neonatal intensive care unit after a bed move, 6 and using the wrong ABO group red blood cells (RBCs) to prime the bypass circuit for an infant undergoing congenital heart surgery. 7 Despite health care leaders recognizing this "identity crisis," we continue to have unacceptable failures in patient identification leading to transfusion of ABO-incompatible blood, incorrect laboratory results, 8 incorrect anatomical pathology specimens, 9 incorrect diagnostic imaging, 10 incorrect surgical procedures, 11 unnecessary delays, patient anxiety, need for sample re-collection, wrong medication administered, unnecessary radiation exposure, wrong breast milk administered, and wrong infant sent home with parents.…”
mentioning
confidence: 99%